Analisis Interaksi Akun Instagram @Tastea.Ig dalam Membangun Brand Image dan Pengaruhnya terhadap Loyalitas Konsumen Muda - Abdillah Abdillah; Angelika Oktavia Popang Rumengan; Nur Azizah Sawir; Yusmanizar Yusmanizar (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
In the era of globalization, the rapid development of information technology has brought significant changes in the way people access and convey information. The presence of the Internet and social media has proven that global networks enable interaction and information exchange to occur in real time without geographical boundaries. One phenomenon arising from this development is social media, which has become a virtual space for individuals and companies to communicate directly, personally, and interactively. One of the most popular social media platforms today is Instagram, a platform that is now widely utilized by businesses, including those in the culinary industry, to build a strong brand image amid intense competition. This study focuses on the Instagram account @tastea.ig, which makes use of visual content, interactive features, and the comment section to maintain emotional connections and consumer trust. The purpose of this research is to analyze the interaction strategies of the @tastea.ig account in maintaining a positive brand image in the eyes of its followers. Instagram’s visual-centric nature allows businesses to showcase their products in an aesthetically appealing manner, drawing attention from potential customers. The strategic use of high-quality images, videos, and stories not only highlights the brand’s offerings but also creates a lifestyle around the product. @tastea.ig effectively uses these features to build an engaging presence, showing its products in an appealing and relatable context. In addition to visuals, Instagram’s interactive features such as polls, quizzes, and direct messaging foster a sense of community and direct engagement with followers. By involving followers in decision-making or seeking their opinions, @tastea.ig strengthens its relationship with its audience, making them feel valued and heard.